Modelos de aprendizaje automático para la predicción del riesgo de fatalidad por insuficiencia cardiaca con datos clínicos (2021)
The purpose of this user manual of the research project "Machine learning models for predicting the risk of fatality due to heart failure with clinical data", is intended to offer users support for the execution and visualization of the results obtained; Here you will find a brief description of both the physical (Hardware) and the logical (Software) requirements, an installation guide for the necessary programs, which are: Python and libraries such as pandas, scikit-learn, among others; finally the execution and with it the visualization of the concluded results. To achieve the objective of this guide, it is not necessary to have programming concepts, but rather to have computer skills, statistics and mathematics, to achieve the execution and understanding of the results. It is very important to read the instructions completely, to guarantee the expected results